A high-throughput screen to identify novel calcineurin inhibitors - Margassery, L.; Kennedy, J.; O'Gara, Fergal; Dobson, A.; Morrissey, J. (Elsevier Inc, 2012)
Calcineurin is a eukaryotic protein phosphatase important for many signalling and developmental processes in cells. Inhibitors of this enzyme are used clinically and there is interest in identifying novel inhibitors for therapeutic applications. This report describes a high-throughput assay that can be used to screen natural or chemical libraries of compounds to identify new calcineurin inhibitors. The microtitre plate assay is based on a yeast reporter strain and was validated with known inhibitors and tested in a pilot screen of bacterial extracts.